Strategies for early recognition of cutaneous melanoma-present and future - Franziska Brehmer; Marina Ulrich; Holger A. Haenssle (Mattioli1885, 2012)
Cutaneous melanoma is a highly aggressive malignant tumor of skin melanocytes with an increasing incidence in most countries of the world, especially in the fair-skinned populations. Despite all preventive and therapeutic efforts, malignant melanoma is still the most lethal skin cancer. A delayed diagnosis results in an advanced stage and worsened prognosis. Once distant metastases are present, the five-year survival rate is less than 10 percent. At the same time, patients may be cured by an early diagnosis of cutaneous melanoma followed by a wide excision. Therefore, the early detection of melanoma at curable stages is crucial for the patients' survival. Besides the investigation of pigmented lesions with the unaided eye, a wide range of examination techniques for improved diagnostic accuracy have been developed and validated in clinical trials. However, none of these techniques are able to provide a definite and final diagnosis or to replace an excisional biopsy of suspicious lesions followed by histological analysis. This review provides a concise overview of general principles as well as current and future strategies for an improved early diagnosis of cutaneous melanoma.